Toward new partnerships in remote sensing : government, the private sector, and earth science research (National Academies Press, 2002)
Steering committee report of a workshop held in March 2001 at the National Academies in Washington, D.C. titled "Remote Sensing and Basic Research: the Changing Environment" describing relationships and interactions evolving between the scientific community and data providers in the public and private sectors for the production and delivery of remote sensing data for scientific research.